Analytical characterization of tequila (silver class) using stable isotope analyses of C, O and atomic absorption as additional criteria to determine authenticity of beverage. (June 2020) - Fonseca-Aguiñaga, Rocío; Gómez-Ruiz, Humberto; Miguel-Cruz, Floriberto; Romero-Cano, Luis A.
Abstract: In the present work the isotopic characterization of Tequila (n = 75) and Tequila 100% agave (n = 145) was made from samples obtained from the Tequila Regulatory Council (CRT for its acronym in Spanish) using a stratified sampling by proportional allocation. The results obtained for δ 13 CVPDB show that 96% of the data are between −12.0 and −13.5‰, so they can be related to the plant type used as a source of sugar to obtain alcohol ( Agave tequilana Weber blue variety, plant of the group Crasulacean Acid Metabolism). On the other hand, the experimental data for δ 18 OVSMOW showed that 96% of the data are in a range of +16.0 to +24.5‰, which may be they can be defined as an indicator of: a) the water of the region, used during the cultivation of the plant and the production process of the final product and/or b) the average annual temperature to which the plant is subjected, indicating that these parameters can be used to demonstrate that agave has been cultivated in the region that grants the designation of origin. Additionally, for selected samples the determination of copper by atomic absorption was carried out. From the results obtained, the isotopic chart of the beverages was built (δ 13 CVPDB vs. copper content). The sensitivity of the isotopic chart (100%) and its specificity (100%) were determined, evaluating alcoholic beverages from different sources of the Agave tequilana Weber blue variety (grape, corn, wheat, sugarcane, mezcal, bacanora and raicilla). Graphical abstract: Image 1 Highlights: A consistent method was developed to study the authenticity of tequila. The method consists on the use of GC/IRMS and AA spectroscopy. The sensitivity and specificity achieved are 100%, for the number of samples analyzed. The method distinguishes tequila from other beverages produced from differents agave plants (mezcal, raicilla and bacanora). All the samples where provided by CRT which gives certainty to the origin of each sample.